2014
DOI: 10.2319/042814-307.1
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic bracket slot dimensions as measured from entire bracket series

Abstract: Objective: To measure the slot dimensions of an entire series of metal orthodontic brackets. Materials and Methods: Ten bracket series approximating five complete sets of brackets each were imaged and measured. Descriptive statistics were generated. Results: Slot dimension varied significantly from series to series as well as within the series themselves. About one-third of the brackets would not accommodate a full-size wire, and 15% to 20% are 0.001 inches or larger than the nominal advertised size. Conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 4 publications
7
41
1
5
Order By: Relevance
“…Brown et al measured the slot dimensions of 10 bracket series approximating five sets of brackets each and reported that about 30% of the brackets were narrower than expected, whereas 15% to 20% were at least 0.001 in. larger than the nominal value (Brown, Wagner, & Choi, ).…”
Section: Discussionmentioning
confidence: 98%
“…Brown et al measured the slot dimensions of 10 bracket series approximating five sets of brackets each and reported that about 30% of the brackets were narrower than expected, whereas 15% to 20% were at least 0.001 in. larger than the nominal value (Brown, Wagner, & Choi, ).…”
Section: Discussionmentioning
confidence: 98%
“…Changes in the geometry of the bracket and slot can affect orthodontics, so, it is necessary to understand these changes for clinical knowledge (Brown et al, ; Joch et al, ). Moreover, the play between bracket slot and archwire can cancel small structural imperfections of the slot (Dalstra, Eriksen, Bergamini, & Melsen, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a wide variation of brackets prescriptions, some of them promise reducing wire bending and chair time, but orthodontists should be aware that the lack of accuracy of brackets slots can require additional bends at the end of treatment to achieve desired results (Brown, Wagner, & Choi, ; Joch, Pichelmayer, & Weiland, ). Considering that preset brackets are commonly used today, they are listed according to the chosen mechanics, which decreases the number of bends and the query time in orthodontics treatment, although questions remain as to the accuracy of these listings and whether there are imperfections in the slot (Alexander, ; Creekmore, ; McLaughlin & Bennett, ; Meling et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturing anomalies may occur in a single bracket, throughout the sets of specific tooth brackets, or generally throughout an entire bracket series. 15 These manufacturing irregularities hamper efforts to evaluate how bracket slot size may affect the outcomes of orthodontic treatment.…”
Section: 11mentioning
confidence: 99%